Modelling the Additive Functional Equations through RSM Matrices - Narasimman, Pasupathi; Ravi, K; Pinelas, Sandra (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
This paper suggests one possible method to model additive type of functional equations using eigenvalues and eigenvectors of matrices with suitable numerical examples. The authors have defined a new type of Row Sum Matrix(RSM) and have discussed its eigenvalues and eigenvectors in order to model functional equations. The famous additive cauchy functional equation and Logical functional equation have also been modelled using identity matrix and Logical matrix in this study.